Isocyanide based [4+1] cycloaddition reactions: an indispensable tool in multi-component reactions (MCRs) - Kaur, Tanpreet; Wadhwa, Preeti; Bagchi, Sourav; Sharma, Anuj (Chemical communications (Cambridge, England), 2016)
The advent of cycloaddition reactions in the synthesis of heterocycles and their ever burgeoning applications in the fields of material chemistry, catalysis and drugs have been a profound scientific development. In particular, isocyanide based cycloaddition reactions have been harbingers of an exciting new chapter in the realms of organic synthesis. The emergence of numerous synthetic protocols utilizing formal cycloaddition of isocyanides with conjugated heterodienes has unleashed countless opportunities to design and synthesize diverse heterocyclic scaffolds. To date, there has not been any exclusive review on a formal [4+1] cycloaddition involving isocyanides. The present review highlights the journey of formal [4+1] cycloaddition reactions of isocyanides with diverse electrophilic substrates viz. oxadienes, azadienes, thioacyl imines, alkylidene amides, alkylidene hydrazines, α,β-unsaturated nitro compounds, α-thioxothioamides, nitroso alkenes, acyl imines, vinyl ketenes, vinyl isocyanates, etc. to afford functionalized pyrroles, imidazoles, furans, oxazoles, pyrazoles, etc.